A argumentação de alunos do ensino fundamental na solução de problemas envolvendo expressões aritméticas - Costa, Monize Barros Lima (2022)
This research aimed to analyze the structural and content characteristics of the arguments developed by students of the 7th year of Elementary School, during the resolution of problems involving Arithmetic Expressions. The research, of a qualitative nature, was developed in a public school in the upstate of Bahia and involved the proposition of six questions to the students, four contextualized and two decontextualized, dealing with such content. The arguments produced in response to the proposed questions were analyzed by means of categories presented by Antonio Sales and Toulmin’s Pattern Argument. Due to the Covid-19 pandemic, which led to the suspension of classes from March 17, 2020, the researcher's three meetings with students took place virtually, through the Google Meet platform. Access to the questions by the students occurred through a link made available on the platform, which led them to the questionnaire in Google Forms. The students answered the proposed questions and sent their answers online so that, afterwards a discussion could then take place in the virtual classroom and then they could orally present the reasoning used to solve the questions. There was a systematic investment by the researcher in strategies that supported the exposition of arguments by the students, both orally and in writing, so that it was possible to understand their reasonings. The analysis showed that such investment contributed to the students' adoption of metacognitive thinking, which is one of the several contributions of argumentation. The results indicate the ability of most students with the mathematical operations required in the questions, and that they had difficulties, both for understanding the context of each one of them, and in transforming natural language into mathematical language, through arithmetic expressions. Thus, initially the students showed a certain ability to resolve expressions when decontextualized. However, through the exposition and reflection of their ideas, with the mediation of the researcher, they began to overcome the initial difficulties and resolve, with more autonomy, the contextualized questions. The arguments presented, for the most part, relied on data, conclusions and warrants, with backing being implicit. Considering that the warrants presented mathematical operations and other knowledge of this disciplinary field that connected the data to the conclusion, supporting them, it was considered that most students adopted a rational argument in solving the questions. The research contributes to the understanding of students' reasoning about the content Arithmetic Expressions, as well as to the valorization of argumentation as a didactic strategy allied to the teaching of this content in a contextualized way, to overcome a teaching based on the application of algorithms and memorization.